2013
DOI: 10.3399/bjgp14x676393
|View full text |Cite
|
Sign up to set email alerts
|

Use of alarm features in referral of febrile children to the emergency department: an observational study

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…The parent decision-making and risk assessment leaflet "How to recognize if your child is seriously ill" was developed with parents for parents (Electronic Supplementary Material 1). The content was designed using the NICE "Fever in under 5s: assessment and initial management" (13), pediatric sepsis guidelines, sepsis leaflets for parents (14)(15)(16), and studies reporting signs and symptoms of children presenting to pediatric emergency departments (17,18). Based on the available evidence, the content of the risk assessment symptoms refers to preschool and primary school children, generally below 12 years of age.…”
Section: Parent Leafletmentioning
confidence: 99%
“…The parent decision-making and risk assessment leaflet "How to recognize if your child is seriously ill" was developed with parents for parents (Electronic Supplementary Material 1). The content was designed using the NICE "Fever in under 5s: assessment and initial management" (13), pediatric sepsis guidelines, sepsis leaflets for parents (14)(15)(16), and studies reporting signs and symptoms of children presenting to pediatric emergency departments (17,18). Based on the available evidence, the content of the risk assessment symptoms refers to preschool and primary school children, generally below 12 years of age.…”
Section: Parent Leafletmentioning
confidence: 99%
“…There have, however, been rare case reports of reversible renal insufficiency in children with febrile illness treated with ibuprofen or other NSAIDs, largely associated with volume depletion [ 60 62 ]. Dehydration is common in children with fever [ 63 ] and is an important risk factor for NSAID-induced acute renal failure; this has led some experts to recommend caution with ibuprofen use in children with dehydration or pre-existing renal disease [ 1 , 22 ]. Recently, a retrospective chart review of 1,015 children with AKI managed over an 11.5-year period concluded that 27 cases (2.7 %) were associated with NSAID use (predominantly ibuprofen), and that younger children (<5 years of age) were more likely to require dialysis or admission into intensive care units [ 64 ].…”
Section: Treating the Distressed Feverish Childmentioning
confidence: 99%
“…In addition, we assumed that all referred children would have had an alarming symptom; if this was not the case, then this assumption would slightly overestimate the prevalence of SI among children with an alarming symptom. 15 A similar effect in children without an alarming symptom will be negligible because of the small numbers involved.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…When Ն3 alarming symptoms were present, nearly all children were referred. 15 A child was triaged as "self-care advice" and received telephonic advice only if none of the above findings were present. A trained research nurse visited all children (regardless of their triage results) at home within 24 hours of inclusion (median, 14 hours; range, 5-21 hours).…”
Section: Methodsmentioning
confidence: 99%